Preparation, characterization, and biocompatibility evaluation of poly(Nɛ-acryloyl-l-lysine)/hyaluronic acid interpenetrating network hydrogels. (20th January 2016) - Cui, Ning; Qian, Junmin; Xu, Weijun; Xu, Minghui; Zhao, Na; Liu, Ting; Wang, Hongjie
Highlights: Poly( N ɛ -acryloyl-l -lysine)/hyaluronic acid hydrogels were prepared by hydrazone bond crosslinking and photo-crosslinking. Poly( N ɛ -acryloyl-l -lysine)/hyaluronic acid hydrogels exhibited a good shape recovery property. Poly( N ɛ -acryloyl-l -lysine)/hyaluronic acid hydrogels showed a glutathione-responsive degradation behavior. Poly( N ɛ -acryloyl-l -lysine)/hyaluronic acid hydrogels exhibited good in vitro and in vivo biocompatibility. Abstract: In the present study, poly( N ɛ -acryloyl-l -lysine)/hyaluronic acid (pLysAAm/HA) interpenetrating network (IPN) hydrogels were successfully fabricated through the combination of hydrazone bond crosslinking and photo-crosslinking reactions. The HA hydrogel network was first synthesized from 3, 3′-dithiodipropionate hydrazide-modified HA and polyethylene glycol dilevulinate by hydrazone bond crosslinking. The pLysAAm hydrogel network was prepared from N ɛ -acryloyl-l -lysine and N, N ′-bis(acryloyl)-(l )-cystine by photo-crosslinking. The resultant pLysAAm/HA hydrogels had a good shape recovery property after loading and unloading for 1.5 cycles (up to 90%) and displayed a highly porous microstructure. Their compressive moduli were at least 5 times higher than that of HA hydrogels. The pLysAAm/HA hydrogels had an equilibrium swelling ratio of up to 37.9 and displayed a glutathione-responsive degradation behavior. The results from in vitro biocompatibility evaluation with pre-osteoblasts MC3T3-E1 cells revealed that the pLysAAm/HA hydrogels could support cell viability and proliferation. Hematoxylin and eosin staining indicated that the pLysAAm/HA hydrogels allowed cell and tissue infiltration, confirming their good in vivo biocompatibility. Therefore, the novel pLysAAm/HA IPN hydrogels have great potential for bone tissue engineering applications.